1980
DOI: 10.1111/j.1751-0813.1980.tb02580.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Alpha‐tocopherol Levels in Livers of Weaner Sheep With Nutritional Myopathy

Abstract: Outbreaks of ovine weaner nutritional myopathy occurring in the southwest of Western Australia outside the recognised selenium-responsive areas have been investigated. One hundred and five sheep died in 3 outbreaks following 5 months grazing cereal stubble paddocks. Liver selenium and glutathione peroxidase activities, measured as an index of biological availability of dietary selenium, indicated that the selenium status of the animals was probably adequate. A comparison fo liver selenium and alpha-tocopherol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…It was concluded that during vitamin E depletion in sheep a-tocopherol concentration in plasma was a good index of vitamin E status under the experimental conditions employed. a-Tocopherol : Vitamin E : Nutritional myopathy : Sheep Vitamin E deficiency can be an important factor in the development of nutritional myopathy in ruminants (Steele et al 1980;. Measurements of atocopherol in plasma are used as an index of vitamin E status in ruminants which assumes that there is a direct relationship between the plasma and the tissue concentrations of atocopherol (McMurray et al 1983).…”
mentioning
confidence: 99%
“…It was concluded that during vitamin E depletion in sheep a-tocopherol concentration in plasma was a good index of vitamin E status under the experimental conditions employed. a-Tocopherol : Vitamin E : Nutritional myopathy : Sheep Vitamin E deficiency can be an important factor in the development of nutritional myopathy in ruminants (Steele et al 1980;. Measurements of atocopherol in plasma are used as an index of vitamin E status in ruminants which assumes that there is a direct relationship between the plasma and the tissue concentrations of atocopherol (McMurray et al 1983).…”
mentioning
confidence: 99%
“…As no clinical or histological symptoms of white muscle disease were found (e.g., via heart histology), the concentrations of VitE in serum were in the normal range, and the animals were younger than most described in literature, it still cannot be concluded that the lambs and kids were actually deficient in VitE. Additionally, Steele et al. (1980) defined that only VitE concentrations of less than 1 μ g/g liver of weaner sheep is said to be deficient.…”
Section: Discussionmentioning
confidence: 97%
“…To a large extent, therefore, the ruminant now requires tocopherol only to overcome the toxic effects of excess PUFA in the diet, or to prevent lipid peroxidationand membrane damage in the absence of the far more efficient glutathione peroxidase. The only report of nutritional myopathy in ruminants with seemingly adequate selenium levels (and not obviously receiving excess PUFA) is that described in Western Australia (43) where weaner sheep grazed cereal stubble and were given cereal grain supplements. Low tocopherol levels (0.6-0.9 mg/kg) were found in the livers of these sheep.…”
Section: Ruminant's Tocopherol Requirementsmentioning
confidence: 96%
“…(27) Levels as low as 0.7 mg/kg have been reported for dry summer feed grazed by sheep in some areas of Western Australia. (43) After harvesting and during storage, the tocopherol content of pasture and other crops may fall further. sometimes to zero.…”
Section: Tocopherol Intakementioning
confidence: 99%